Design of 2.75-2.85 Ghz Frequency Microstrip Band Pass Filter with Square Open-Loop Resonator in Radar Method - Faroqi, Adam; Ali Ramdhani, Muhammad; Dwi Andika, Dzikron; Soedarsono, Suryadi (International Journal of Engineering and Technology, 2018)
Radar is an important component for people. A number of functions could be taken into account on a various aspect in term of quantifying the distance of a specific object, developing a map, and/ or forecasting climate. Generally, one of the main instruments within a radar is a filter. The aim of this study is to design a simple Band Pass Filter which able to be effectively worked on frequency 2.75–2.85 GHz. The filter is designed at the mid frequency of 2.8 GHz with ≤ -20 dB of Return Loss Range, ≥ -3 dB for Insertion Loss, and 100 MHz for Bandwidth, then it is manufactured into a Square Open-Loop Resonator microstrip. The filter uses Rogers R04035B for its substrate with 3.48 of Dielectric Constant Values  and 1.524 mm of Substrate Thickness (h). The radar’s filter is simulated by a software of Computer System Technology (CST) suite 2015. The simulation results -31.608995 dB for Return Loss Range, -2.0529871 dB, and 100 MHz for Insertion Loss and Bandwidth respectively. By the end of this process, this instrument is applied and a Network Analyzer is then utilized to get a comparable output. It produces a quite different ranges of -23.519 dB for Return Loss, -2,183 dB for Insertion Loss and 90 MHz for Bandwidth.  The study results a design of radar’s simple band pass filter which work effectively on frequency 2.75–2.85 GHz.